Cognitive skills, personality traits and dropout in Dutch vocational education - Irene Eegdeman (Empirical Research in Vocational Education and Training, 2018)
Abstract Designing effective educational programs to reduce dropout in higher and vocational education requires thorough understanding of the underlying mechanisms of study success. This study examines if first-year dropout is associated with cognitive ability and personality traits as measured by a formative entry test just before enrollment in Dutch vocational education. The results show that the formative entry test outcomes do not properly identify students at risk, the association between first-year dropout and, respectively, cognitive skills and personality traits is generally not significant. Consequently, and of importance for both students and vocational education institutes, students cannot be properly informed about whether their skills and personality traits match the required skills and personality traits of the program.